Effects of monolaurine, acetic acid, and EDTA on thermal inactivation of Escherichia coli (UPCC 1195) in ground chicken meat - Dela Fuente, Ma. Cecilia A. (C0llege of Home Economics, University of the Philippines, 2009)
ABSTRACT This study aimed to determine the effect of monolaurin, acetic acid, and ethylenediaminetetraacetic acid (EDTA) on the thermal inactivation of Escherichia coli (UPCC 1195) in ground chicken breast meat. The optimum concentration of monolaurin necessary to significantly reduce E. coli count in ground chicken breast meat was initially determined. There was no significant difference between various concentrations; thus, the lowest concentration, 1000 μg/ml was used. Then, the efficacy of 1000 μg/ml monolaurin, in combination with 21.5 mM acetic acid and/or 156 μg/ml EDTA, was established. The optimized antimicrobial system that showed significant (P<0.05) effect on E.coli count was the combination of monolaurin and EDTA. The optimum combination of monolaurin and EDTA was used for the thermal inactivation studies. The decimal reduction times (D-values) of E. coli at 55°C and 60°C, together with the optimized antimicrobial system, were calculated as 15.838 and 10.044, respectively. Further study is recommended to compare the effect of heat treatment with and without antimicrobial treatment.